A novel approach for measuring bubbles uniformity and mixing efficiency in a direct contact heat exchanger. (15th December 2015) - Fei, Yu; Xiao, Qingtai; Xu, Jianxin; Pan, Jianxin; Wang, Shibo; Wang, Hua; Huang, Junwei
Abstract: This paper presents a straightforward method for assessing the uniformity and mixing time of bubbles based on uniform design in a direct contact heat exchanger. The evolution of bubbles movement is experimentally tracked using an imaging technique that is processed in the Matlab software to obtain the local bubble concentration. The local discrepancy of a set of bubbles seems to be a useful concept to measure the difference between theory and empirical distribution. The UC (uniformity coefficient) is associated with a discrepancy, leading to a useful parameter to characterise the mixture homogeneity and mixing time. To determine the impact of expressions, iteration steps and pixels on the measurement, evolution of UC response frames are investigated. The mixing time and uniformity obtained by UC method were compared with data obtained by Betti numbers method. The simulations and experiments between local and global uniform (with the same Betti numbers) are discussed and examples are given for illustration. The results show that the space-time features of the mixing process have been successfully derived by UC method. The UC curves bring new insights to study and compare mixing efficiency of different systems, which has a high degree of reliability, and can yield accurate mixing information. Highlights: A novel approach for measuring bubbles uniformity and mixing efficiency is proposed. The simulations and experiments are discussed and examples are given for illustration. Evolution of uniformity coefficient response frames are investigated and compared. The space-time features of the mixing process are successfully derived.